泰国不同行业中文学习者的学习策略分析 - Nawanan Woraditnitiwaraatorn (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2024)
At present, Chinese language has become one of the languages with the largest number of learners worldwide. Learners are no longer confined to schools, but also include professionals from all walks of life. However, due to the different learning objectives of practitioners in different industries, they attach different importance to language skills, which leads to their different learning strategies. This study focuses on interviewing Thai Chinese learners from different industries to investigate their strategies to improve their Chinese language level in the professional environment. In this study, interviews and questionnaires were used to investigate Chinese learners in different industries in Thailand, in order to understand the learning strategies they adopted in their professional background. The results show that the participants generally recognize the importance of mastering specific language skills in their own professional fields, and the learning strategies they choose are closely related to their occupations. The research results are expected to provide useful information for the field of Chinese teaching, especially in the teaching of Chinese vocational education, which has been widely increasing attention in recent years.